Does the Minimum Wage Affect Employment? Evidence from the Manufacturing Sector in Indonesia - Del Carpio, Ximena; Nguyen, Ha; Wang, Liang Choon (World Bank, Washington, DC, 2012)
Using survey data from the Indonesian manufacturing industry, this paper investigates the impact of minimum wage on employment and wages offered by Indonesian manufacturing firms from 1993 to 2006. It shows that the estimated effects of minimum wage on employment are positive within a province (i.e., with province fixed effects), but negative within a firm (i.e., with firm fixed effects), indicating the importance of using firm panel data to reduce the endogeneity bias in estimates. It finds significant heterogeneous effects of minimum-wage changes on employment. The employment effects of minimum wages are significant and negative among small firms and less educated workers, but not among large firms and workers with high school education and above. The negative employment impact is more severe for non-production workers than for production workers. The analysis also shows that the minimum wage disproportionally affects women: most of the non-production job losses are experienced by female workers. Lastly, the paper finds that the minimum wage is more correlated with the average wage of small firms than that of large firms, suggesting that minimum wages are more binding in small firms.